(untitled) (Nigerian Journal of Technology, 2021)
The 20–25 years economic life for hydrocarbon pipelines in the investment decision model is at wide variance with historical statistical records of more than 90-percent world-wide. Opinions diverge, from service type to the product quality, and materials resilience as basis for this premise. While, financial experts consider time to fully depreciate a capital investment, irrespective of the rate of returns, engineers consider operational availability and reliability duration. The risk is that actual residue values of pipelines worldwide are erroneously omitted in every project’s economics Cash-flow computation, thus eroding the investment decision quality. Statistics showed that more than 60-percent of pipelines worldwide have already exceeded the 25 years economic life, while more than 40-percent have operated more than 30-years and above. This theoretical appraisal identified a gap in the economic model in handling multi-criteria risk management uncertainties like hedging, weighting, etc., and highlighted the exigency to craft and assign numeric residue values for pipelines in the investment Cash-flow models. http://dx.doi.org/10.4314/njt.v40i2.7